Problem Pluralisme Agama - Harda Armayanto (Universitas Darussalam Gontor, 2014)
As a part of liberal theology, the tenet of religious pluralism suggests tolerant systems toward all religious adherents. However, this tenet turned out to cause new problems for religious adherents. It is because of religious pluralism has the concept of truth relativism. This term has the doctrine that there is no absolute truth of each religion, as the acceptance of all religious paths as equally valid. Stating that all religious paths are equally valid, the bearers of religious pluralism hope no longer a religion that claims to be the owner of the ultimate truth because in essence, religion is the result of a variety of human feelings and religious experience, so every religion that exists in this world contains divine truth. Many religious experts did not agree with this worldview and they actually considered it a new religion that wants to unite all religions. Through this article, the author wants to prove that religious pluralism is a fierce polemic and it could cause many problems in religions. Although it has a good goal, it is very problematic to understand. In fact, many religions have turned out to reject this understanding. There are some movement of many religious experts shows that notion of pluralism is problematic, as containing polemical and highly problematic issue for instance when applied in the existing religions. Every religion saw religious pluralism is only a disguise to erode the confidence of believers who in turn gave rise to the atheists. Eventually, the adherents of each religion will be skeptical towards religion.